Statin use and acute kidney injury among hospitalized chronic kidney disease patients: a retrospective cohort study - Tang, Ling-Er; Xu, Da-Min; Xu, Ling-Yi; Zhao, You-Lu; Zhu, Yi-Dan; Lv, Ji-Cheng; Yang, Li; Zheng, Xi-Zi (Frontiers in Medicine, 2025)
BackgroundChronic kidney disease (CKD) constitutes a substantial burden in terms of cardiovascular disease and acute kidney injury (AKI). While statins are recommended for their cardiovascular benefits in CKD patients, their impact on AKI remains inconclusive.MethodsA retrospective screening was conducted on all adult hospital admissions from January 1, 2018, to December 31, 2020, including patients with CKD. Statin exposure was defined as any prescription within 48 h of admission. Patients were monitored until death, discharge, or a maximum of 30 days. The primary outcome was in-hospital AKI, with in-hospital mortality as the secondary outcome.ResultsIn a cohort of 5,376 patients, the median age was 72 years; 3,184 (59.2%) were male, and 2,129 (39.6%) were statin users. In-hospital AKI was observed in 149 (7.0%) of statin users compared to 213 (6.6%) of non-users. Statin use was significantly associated with a reduced risk of in-hospital AKI [adjusted hazard ratio [aHR], 0.74; 95% confidence interval [CI], 0.56–0.96] and in-hospital mortality (aHR, 0.45; 95% CI, 0.24–0.88). These outcomes were consistent across subgroup analyses stratified by age, gender, baseline estimated glomerular filtration rate (eGFR), and cardiovascular disease (all P for interaction >0.05), as well as in sensitivity analyses excluding patients who discontinued statin therapy during hospitalization or initiated statin therapy post-baseline. Among atorvastatin users (63.4%, 1,350/2,129), only medium-dose atorvastatin was significantly associated with reduced risk of in-hospital AKI after full adjustment (aHR, 0.68; 95% CI, 0.49–0.95).ConclusionsStatin use may improve survival and reduced AKI risk in hospitalized patients with CKD, with atorvastatin showing particularly favorable renoprotective effects.